Immune-related hub genes and their role in psoriasis pathogenesis - Tingting Yin; Tingting Zhang; Lei Ma (Scientific Reports)
Abstract Psoriasis is a prevalent inflammatory skin disorder with immune-related mechanisms that remain incompletely understood. To elucidate the immune landscape of psoriasis, we analyzed expression profiles to identify 115 psoriasis susceptibility genes (PSGs) and subsequently pinpointing eight immune-related hub genes (IRHGs). A predictive model incorporating these IRHGs demonstrated promising prognostic potential for psoriasis. Additionally, extensive intercellular communication was observed among keratinocytes, dendritic cells, monocytes, and T cells. The cellular differentiation trajectory revealed a complex interplay among various cell types and states, highlighting genes such as CXCL8, CCL2, STAT3, and STAT1 emerging as closely associated with the cellular composition and functional status within the psoriatic immune microenvironment. The present study may shed light on the understanding of the immunopathological dynamics of psoriasis and the development of novel therapeutic strategies and biomarkers for this multifaceted skin disorder.